Osteossíntese umeral em pombos domésticos (Columba lívia) por xenoenxerto ósseo, conservado em mel tratados ou não com laser arseneto de gálio (AsGa) - Gomes, Kleber Tochetto (2010)
The increase in attendance of wild animals, especially birds, leads to the veterinarian deal with numerous diseases in these animals, being the fractures one of the most frequent injuries in the veterinary clinical surgery. The aim of this study was to reduce the recovery period of birds with humeral fracture in order to anticipate the release of them back into the environment. It was used 32 pigeons which were randomly divided into two groups consisting of 16 animals each. Animals from both groups were undergone osteosynthesis of the humerus using xenograft preserved in honey. Group I or control (GI) received no additional treatment, while in the Group II (GII) was treated with Gallium arsenide laser (GaAs) for seven days postoperatively using punctual application and dosimetry of 4 J/cm2. Each group was subdivided into four groups containing four animals each according to the evaluation period (8, 15, 30 and 60 days). The animals were evaluated clinically once daily throughout the postoperative period, starting at early postoperative period. All birds were evaluated radiologically at early postoperative period and weekly until the period for the histological evaluation of each animal. Histological evaluation did not differ between groups. It was observed an intense formation of cartilaginous tissue at 8 and 15 days, nevertheless it was possible to observe early formation of bone trabeculae at 15 days in the cartilage formation. At 30 days the callus was composed of trabecular bone with some cartilage, and 60 days this callus had been consolidated by trabecular bone with low cellular activity. The callus formation was observed only in 30 days in the radiographic evaluation. Clinically, the birds evidenced functional use of the limb, absence of edema, discharge or signs of infection. In the flight test, all animals from GII reached flight until 19 days after surgery, whereas GI only at 23 days postoperatively. It was concluded that the use of an intramedullary bone pin from metatarsal of cats and preserved in honey, introduced in a retrograde way for humeral osteosynthesis in pigeons are highly feasible. The radiation therapy with Gallium Arsenide laser (GaAs) (4 J/cm2) applied at four points decreases the time for restoring the flight.